Identical genetic control of MLC reactivity to different MHC incompatibilities, independent of production of and response to IL-2 - Holán, V; Lipoldová, M; Demant, P (Immunogenetics, 1996)
The inbred strain STS/A exhibits a higher proliferative response in the mixed lymphocyte culture (MLC) to stimulator cells of all 11 tested inbred mouse strains with 10 different major histocompatibility complex (MHC) haplotypes, as well as to stimulation with IL-2 than does the strain BALB/cHeA. However, alloantigen-stimulated BALB/c cells produce more IL-2 than STS/A cells. To study the genetic basis of these differences, we used 20 recombinant congenic strains (RCS) of the CcS/Dem series. Each of these CcS/Dem RC strains contains a different subset of about 12.5% of genes from the STS/A strain and the remaining approximately 87.5% of BALB/c origin genes. As a result the multiple non-linked genes responsible for phenotypic differences between BALB/c and STS/A became separated into different CcS/Dem strains. The strain distribution pattern (SD) of high or low MLC response of individual CcS/Dem strains to stimulator cells of four different strains was almost identical, indicating that differences in responsiveness, rather than the alloantigenic difference itself, determine the magnitude of the response, and that the responsiveness to different alloantigens is largely controlled by the same genes. The SDP of IL-2 stimulation was different from that of MLC responsiveness. The differences in the proliferative responses observed among individual CcS/Dem strains were not due to differences in numbers of CD3+, CD4+ or CD8+ cells or to the observed differences in IL-2 production, and hence they likely reflect genetically determined intrinsic properties of T cells. These results show that a set of non-linked genes controls proliferative responses in MLC irrespective of the MHC haplotype of the stimulator cells, and that stimulation with IL-2 and production of IL-2 are controlled by different subsets of genes. Since the genomes of all RCS are extensively characterized by microsatellite markers, they can be used to map the genes controlling proliferative responsiveness to stimulation with alloantigens and IL-2.
Keywords: interferon gama; Major Histocompatibility Complex; Interleukin-2; Interferon-gamma; kultivované buňky; Mice, Inbred BALB C; CD3 Complex; interleukin-10; Mice; slezina; interleukin-2; Cells, Cultured; CD8-pozitivní T-lymfocyty; aktivace lymfocytů; zvířata; Lymphocyte Activation; Lymphocyte Culture Test, Mixed; myši inbrední BALB C; antigeny CD3; myši; CD4-pozitivní T-lymfocyty; test smíšené lymfocytární kultury; hlavní histokompatibilní komplex; T-Lymphocyte Subsets; Interleukin-10; CD8-Positive T-Lymphocytes; Spleen; T-lymfocyty - podskupiny; CD4-Positive T-Lymphocytes; Animals